Urgensi Pengaturan Budaya Reyog Ponorogo Perspektif Hukum Kritis Dan Fiqh Siyasah - Wiranti, Indah Wiranti (El-Dusturie, 2024)
This research discusses the urgency of regulating the cultural heritage of Reyog Ponorogo with a focus on the perspectives of critical legal studies and Fiqh Siyasah. The Reyog Ponorogo culture is considered important as part of the national identity but faces serious challenges, especially after the claim attempts by Malaysia in 2007. These philosophical factors have hindered Reyog Ponorogo from receiving recognition from UNESCO. The research questions in this study are: How does the epistemology of critical legal studies relate to the urgency of regulation for the advancement of Reyog culture in Ponorogo? What is the view of Fiqh Siyasah regarding the urgency of regulating Reyog Ponorogo as an effort to promote culture? This thesis is a normative juridical study with a statutory approach and a conceptual approach. The data collection technique involves gathering coherent library materials related to the researched object. From the research conducted during the thesis, it can be concluded that from the epistemology of critical legal studies, regulating the culture of Reyog Ponorogo is a critical step to prevent misuse or unauthorized recognition of the culture. Critical law views the importance of clear regulatory systems to prevent similar cases and as a form of fair copyright enforcement for the people of Ponorogo. From the perspective of Fiqh Siyasah Dusturiyah, regulating the culture of Reyog Ponorogo is an implementation of legal values ​​emphasizing the need for the government to play an active role in preserving and developing cultural heritage. This aligns with the principles of Fiqh Siyasah Dusturiyah, which demand that the government ensure the sustainability of traditions and cultures that are integral parts of its people's identity. The advancement of Reyog Ponorogo culture can also be seen as a strategy to achieve collective welfare goals, involving future generations in cultural heritage.